Penggunaan Media Huruf Balok pada Anak Usia Dini Perspektif Psikoanalitik - Qoni’ah Al Munasiroh; Raden Arasy Bintang M; Rana Dinar A (Journal Innovation In Education, 2025)
This study aims to evaluate the effectiveness of using letter blocks compared to conventional teaching methods in enhancing reading skills, text comprehension, and cognitive development in children aged 5–6 years. This review also examines literature from a psychoanalytic perspective to understand the impact of interactions between children and learning aids on their emotional development. The results indicate that the letter block method is more effective in increasing emotional engagement and multisensory learning, while conventional methods provide structure and discipline in literacy education. A combination of both approaches is recommended for a holistic learning experience.